The Community-Based Moderate Islamic Education (An Ethnographic Study in Pulopancikan Village, Gresik) - Rozi, Khodijah; Yenuri, Ali Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pulopancikan Village is known as a harmonious multicultural community, where people from various religious and ethnic backgrounds live side by side with full tolerance. This harmony cannot be separated from the role of moderate Islamic education based on the community. This study aims to describe and analyze how moderate Islamic education contributes to building tolerance in Pulopancikan Village. With a qualitative ethnographic approach, this study explores the values ​​of moderate Islam applied by the community, such as mutual respect, tawassuth (moderation), at-ta'arruf (getting to know each other), at-tasamuh (tolerance), at-ta'awun (cooperation), and at-tawazun (balance). The results of the study indicate that moderate Islamic education in this village is supported by active communication between religious leaders, village heads, and the community, as well as regular meetings to discuss various social issues. These findings strengthen the idea that community-based education can be an effective strategy in building social harmony.